Prevalence and determinants of chronic malnutrition among preschool children: a cross-sectional study in Dhaka City, Bangladesh - Jesmin, Aklima; Yamamoto, Shelby; Malik, Ahmad Azam; Haque, Md. Aminul (Journal of health, population and nutrition, 2011)
Chronic malnutrition is one of the major causes of morbidity and mortality among preschool children and the future productivity of nations. To understand the prevalence of chronic malnutrition and to identify the factors affecting height-for-age z-score (HAZ) among preschool children, a cross-sectional study was conducted among 380 randomly-selected children aged less than five years in Dhaka city, Bangladesh. Results of analysis of this study data revealed that the prevalence of stunting among preschool children in Dhaka city was 39.5%, with 25% severely stunted and 14% moderately stunted (p<0.001). Results of bivariate analysis revealed that socioeconomic and demographic factors were most significantly associated with the stunting of children. Children were found to be well-nourished if their parents had a tertiary-level education or higher and if the mother held a job and had good knowledge of nutrition. Well-nourishment of the children were also associated with the height of mothers (above 148 cm), good family educational background, normal birthweight, greater frequency of food intake (more than six times/day), and fewer fever episodes in the last six months. Results of multivariate linear regression models showed that height of mothers, birthweight of children, education of fathers, knowledge of mothers on nutrition, and frequency of feeding were the most significant factors that had an independent and direct influence on the stunting of children. To achieve the Millennium Development Goal target of 34% malnutrition prevalence by 2015, it is important to have specific government intervention to focus on the causes that directly influence the stunting of children.